Ethnic Differences in Health among Elderly People Living in Northern Chile - Gallardo Peralta, Lorena Patricia (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2016)
This research analyzes the differences in health in a native Chilean ethnic group of the region of Arica and Parinacota. This is one of the first investigations in Chile and South America that analyzes this in the aging process. The sample consists of 493 Chilean elderly living in the north of Chile in urban and rural areas, including villages in the Chilean Altiplano. The questionnaire was conducted through personal interviews. Scales internationally recognized geriatric research to measure the presence of impaired health, dependence and depression symptoms were applied. The results showed significant differences in depression and health in terms of ethnic belonging, with a disadvantage for the elderly Indians. The aging process is heterogeneous and the cultural aspects through belonged to a native ethnic group are important. For the field of social sciences it confirms the need for gerontological contextualized interventions that positively discriminate against groups at risk.